Perbandingan Aturan Perlindungan Privasi Atas Data Pribadi Antara Indonesia Dengan Beberapa Negara - Tsamara, Nadiah (Jurnal Suara Hukum, 2021)
The development of information and communication technology shows a significant increase. In the development of information technology and technology, personal information consisting of names, e-mails and cell phone numbers is very valuable data because there is economic value obtained in the business world, but technology can also be very dangerous if its use is not restricted, such as in the case of not protecting personal data, while privacy of personal data is important because it involves a person's dignity and freedom of expression, but data is not protected because in Indonesia there is no obligation in positive law which specifically regulates and provides sanctions for violations. This study aims to discuss the regulation in the perspective of comparative law in Europe, America, Hongkong, Malaysia, Singapore, South Korea, and Japan. This study uses normative legal research using asttutory approach and comparative approach that examines and analyses legal sources. This study discovers that the regulation of personal data protection in Indonesia has not been fully and thoroughly regulated compared to the regulations in several other countries, that there is a need for legal harmonization of personal data protection that is mature and deep